Finite element analysis of fatigue crack growth in CFRP-repaired four-point bend specimens - Huang, Cheng; Chen, Tao; Feng, Siyuan (Engineering structures, 2019)
•CFRP repair can effectively enhance the fatigue life of edge-cracked FPB specimens.•A Python-based FE method is developed for the automated fatigue crack modelling.•The simulated failure modes, crack trajectories and fatigue life are validated experimentally.•Repair effects increase with KI/KII, CFRP layer number, width and Young’s modulus.•Mode I appears to dominate the final crack growth under mixed mode I/II fatigue. This paper presents a finite element (FE) study on fatigue crack growth in carbon fiber–reinforced polymer (CFRP) repaired four-point bend (FPB) specimens with an edge crack subjected to various cyclic loadings (pure mode I, pure mode II and mixed mode I/II). The crack propagation rate was described using NASGRO model together with Tanaka formula, while the crack growth direction was determined by maximum circumferential stress criterion (MCSC). A simulation program was developed using Python scripting in conjunction with FE software ABAQUS to handle the automated fatigue crack growth modelling. The effects of different shear-tension loading ratios (KII/KI) and CFRP layer numbers on CFRP repair performance were first investigated by a comparative analysis of numerical and experimental results. The FE results appeared to be in reasonable agreement with test data in terms of specimens’ failure modes, crack growth trajectories and fatigue lives. Based on the developed program, a parametric study was conducted to gain a deeper insight into the effects of KII/KI ratios, the patching layer number, Young’s modulus and width of CFRP on FPB specimens’ fatigue behavior. The results indicated that the above-mentioned parameters have a significant influence on fatigue crack growth to varying degrees. This work provides an effective way of predicting the fatigue life and mixed mode I/II crack growth trajectories with high computational efficiency and accuracy.